Analysis of Transportation Mode Choices Among Students at Campus B, Faculty of Education and Educational Sciences Pattimura University, Ambon - Bayu Wally; Juliet G. Metekohy (Edunity Kajian Ilmu Sosial dan Pendidikan, 2026)
Transportation plays an essential role in supporting students’ mobility in accessing educational facilities, especially in urban areas with diverse transportation alternatives, such as Ambon City. Students at Campus B, Faculty of Teacher Training and Education, Pattimura University, rely on various transportation modes, including public transportation, private vehicles, and online transportation services. This study aimed to analyze the factors influencing students’ transportation mode choices and to determine the probability of each transportation mode being selected. This research employed a quantitative approach using the stated preference method. Data were collected through questionnaires distributed to 100 students and analyzed using the Statistical Package for the Social Sciences (SPSS). The variables examined included travel cost, travel time, safety, and comfort. The results showed that public transportation was the most frequently chosen mode, with a probability value of 43%, followed by private transportation at 36% and online transportation at 21%. The findings also indicated that travel cost, comfort, safety, and travel time significantly influenced transportation mode selection, both partially and simultaneously. Public transportation was preferred mainly because of its affordability, while comfort became the dominant factor in choosing private and online transportation. In conclusion, transportation mode selection among students is strongly influenced by economic and service-quality considerations, highlighting the importance of improving transportation accessibility and comfort for students in Ambon City.